Extracellular matrix degrading enzyme with stroma-targeting peptides enhance the penetration of liposomes into tumors - Ikeda-Imafuku, Mayumi; Gao, Yongsheng; Shaha, Suyog; Wang, Lily Li-Wen; Park, Kyung Soo; Nakajima, Mayuka; Adebowale, Omokolade; Mitragotri, Samir (Journal of controlled release, 2022)
Various anti-tumor nanomedicines have been developed based on the enhanced permeability and retention effect. However, the dense extracellular matrix (ECM) in tumors remains a major barrier for the delivery and accumulation of nanoparticles into tumors. While ECM-degrading enzymes, such as collagenase, hyaluronidase, and bromelain, have been used to facilitate the accumulation of nanoparticles, serious side effects arising from the current non-tumor-specific delivery methods limit their clinical applications. Here, we report targeted delivery of bromelain into tumor tissues through its covalent attachment to a hyaluronic acid (HA)-peptide conjugate with tumor ECM targeting ability. The ECM targeting peptide, collagen type IV-binding peptide (C4BP), was chosen from six candidate-peptides based on their ability to bind to frozen sections of triple-negative breast cancer, 4T1 tumor ex vivo. The HA- C4BP conjugate showed a significant increase in tumor accumulation in 4T1-bearing mice after intravenous administration compared to unmodified HA. We further demonstrated that the systemic administration of bromelain conjugated C4BP-HA (C4BP-HA-Bro) potentiates the anti-tumor efficacy of liposomal doxorubicin. C4BP-HA-Bro decreased the number and length of collagen fibers and improved the distribution of doxorubicin within the tumor. No infusion reaction was noted after delivery of C4BP-HA-Bro. C4BP-HA thus offers a potential for effective and safe delivery of bromelain for improved intratumoral delivery of therapeutics. [Display omitted] •Collagen type IV-binding peptide (C4BP) exhibited a high affinity to breast tumors.•Conjugating with C4BP enhanced the tumor accumulation of hyaluronic acid (HA).•Bromelain was conjugated to HA with C4BP (C4BP-HA-Bro), keeping its enzyme activity.•C4BP-HA-Bro enhanced the anti-tumor effect of liposomal doxorubicin.